Spasial Clustering Untuk Memetakan Transfusi Darah Berbasis Website - Fitria, Nur Anisa; Rangkuti, Yulita Molliq; Karo, Ichwanul Muslim Karo (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
One of the hospital needs is the availability of blood stock. Information on blood stocks in hospitals and supporting agencies is very necessary as demand continues to increase. This research aims to develop a Geographic Information System (GIS) using the K-Medoids method for mapping blood transfusions in North Sumatra. The results of Clustering Calculations using K-Medoids obtained the following results: The first group consists of RSUD dr. RM Djoelham Binjai, H. Adam Malik Regional Hospital Medan, Pringadi Regional Hospital Medan City, Deli Serdang Regional Hospital, Sultan Sulaiman Syarif Regional Hospital, Dr. Hardianus Sinaga, Batu Bara Regional Hospital, Haji Abdul Manan Simatupang Regional Hospital, Salak Regional Hospital. consisting of UDD: PMI Medan City, PMI Deli Serdang Regency, PMI Batu Bara Regency, UDD PMI Labuhan Batu. The second group consists of Tanjung Pura Regional Hospital, Dr. H. Pane Group, Sidikalang Regional Hospital, Porsea Regional Hospital, Dolok Sanggul Regional Hospital, dr.FL Regional Hospital. Tobing Sibolga, Pandan Regional Hospital, South Tapanuli Regency Regional Hospital, Pasambungan Regional Hospital. consisting of UDD: PMI Pematang Siantar City, PMI Tebing Tinggi City, PMI Asahan, PMI Labuhan Batu Utara, PMI South Tapanuli Regency, PMI Mandailing Natal. The results of the clustering test using the Silhoutte index obtained a value of 0.5457267923095698